Risk factors for African swine fever spread in wild boar in the Russian Federation - O. I. Zakharova; A. A. Blokhin; O. A. Burova; I. V. Yashin; F. I. Korennoy (Ветеринария сегодня)
The analysis and assessment of risk factors associated with the occurrence, spread and persistence of African swine fever (ASF) virus in wild boar population are an important tool in determining the strategic measures aimed at eradicating epizootics and mitigating their consequences. A thorough examination of foreign and domestic literature revealed that wild boar population management factors, socio-economic and environmental ones, that mainly account for the density and number of animals were the most significant and associated with the risk of ASF outbreak occurrence in wild animals. In order to identify risk factors for the spread of the disease in wild boar in the Russian Federation Subjects, a regression model was built to examine the relationship between the annual number of ASF outbreaks in wild boar at the municipal raion level, wild boar population density and some other factors for the period between 2007 and 2022. Based on the Subject-level regression modelling results, a positive association between the intensity of the disease outbreaks and wild boar population density was identified in 42.5% of the model regions of the Russian Federation. Other significant factors were the length of roads, the presence of forest cover and outbreaks in domestic pigs. However, on the whole, for all the infected Subjects, the regression model demonstrated the failure of the wild boar population density factor to explain the observed ASF outbreak distribution, and this may be indicative of the existence of other epizootic drivers of the disease spread in the wild. One of such mechanisms may be the persistence of infectious potential in the external environment and in the formed stationary local foci of African swine fever, despite the anti-epizootic measures taken, including the measures aimed at regulating the number of susceptible population – depopulation.